A STUDY ON THE MATHEMATIC STUDENTS’ DIFFICULTIES IN LEARNING ENGLISH AT EDUCATION STUDY PROGRAM OF FKIP USN KOLAKA - Netty Huzniati Andas (British : Jurnal Bahasa dan Sastra Inggris, 2019)
This research was a descriptive research with qualitative approach. It aimed to investigate the difficulties faced by class A students in the Mathematics Education Study Program in mastering four English language skills (Speaking, Writing, Reading, and Listening). The subjects in this study consisted of 26 students who were selected by purposive sampling. To obtain the data, The researchers used two instruments, namely interviews and questionnaires. Questionnaires were distributed to students to find out the information about students’ difficulties, while interviews were submitted to informants to clarify information obtained from the questionnaires. The data were analyzed through three stages; data reduction, data presentation, and drawing conclusions or verification. The results showed that most of the students had difficulties when they learnt English such as lack of vocabulary, low grammar mastery, and pronounciation. These three problem were regarded as the obstacles to them to perform the four English skills. In addition, facilities in learning as well as techniques or methods used by lecturers in the teaching and learning process became the factor influenced students in mastering English.